Market Liquidity, Hedging, and Crashes - Gennotte, Gerard; Leland, Hayne E. (American Economic Review, 1990)
In the absence of significant news, hedging strategies were blamed for the stock market crash of October 1987; but traditional models cannot explain how a relatively small amount of selling could cause so large a price drop. The authors develop a rational expectations model in which prices play an important role in shaping expectations; markets are much less liquid in their model than in traditional models. Discontinuities (or "crashes") can occur even with relatively little hedging. The model is consistent with theories as disparate as Keynes' "beauty contest" insights and Thom's "catastrophe" analysis and suggests means to reduce volatility. Copyright 1990 by American Economic Association.